Tobacco use and outcome in radical prostatectomy patients. (20th March 2017) - Curtis, Alexandra; Ondracek, Rochelle Payne; Murekeyisoni, Christine; Kauffman, Eric; Mohler, James; Marshall, James
Abstract : This article describes original research showing that among prostate cancer patients treated by radical prostatectomy, smoking status is associated with overall mortality. The relationship between smoking status and prostate cancer treatment outcome after radical prostatectomy is less clear. Abstract: Cigarette smoking has been consistently associated with increased risk of overall mortality, but the importance of smoking for patients with prostate cancer (CaP) who are candidates for curative radical prostatectomy (RP) has received less attention. This retrospectively designed cohort study investigated the association of smoking history at RP with subsequent CaP treatment outcomes and overall mortality. A total of 1981 patients who underwent RP at Roswell Park Cancer Institute (RPCI) between 1993 and 2014 were studied. Smoking history was considered as a risk factor for overall mortality as well as for currently accepted CaP treatment outcomes (biochemical failure, treatment failure, distant metastasis, and disease‐specific mortality). The associations of smoking status with these outcomes were tested by Cox proportional hazard analyses. A total of 153 (8%) patients died during follow‐up. Current smoking at diagnosis was a statistically significant predictor of overall mortality after RP (current smokers vs. former and never smokers, hazards ratio 2.07, 95% confidence interval [CI]: 1.36–3.14). This association persisted for overall mortality at 3, 5, and 10 years (odds ratios 2.07 [95% CI: 1.36–3.15], 2.05 [95% CI: 1.35–3.12], and 1.8 [95% CI: 1.18–2.74], respectively). Smoking was not associated with biochemical failure, treatment failure, distant metastasis, or CaP‐specific mortality, and the association of smoking with overall mortality did not appear to be functionally related to treatment or biochemical failure, or to distant metastasis. Smoking is a non‐negligible risk factor for death among CaP patients who undergo RP; patients who smoke are far more likely to die of causes other than CaP.